Investigation of the constituents of Piper betle Linne (Family Piperaceae) - Rimando, Agnes M. 1957-
Investigation of the constituents of Philippine Piper betle Linne revealed that the major component of the volatile oil is chavibetol and not its isomer eugenol. This was proven from both instrumental and chemical analyses. Chavibetol makes up 53.1% of the oil while eugenol only 0.42%. Chavibetol acetate was detected as the second major component of the oil (15.5%) through GC and combined GC-MS analyses, with the use of a glass capillary column. The presence of chavibetol acetate in Piper oils has never been reported in literature. The other constituents of the oil that were identified are alpha- and beta- pinene, camphene, d-limo-nene, 1, 8-cineole, para-cymene, caryophyllene, safrole, methyl chavibetol (methyl eugenol), 4-allyl(pyro)catecholdiacetate, and 4-allyl(pyro)catecholmonoacetate. Chavicol, which is a characteristic constituent of Piper oil, was not found. From the ether fraction of the leaves, 4-allyl(pyro)catechol was isolated (44.0% yield) by preparative liquid chromatography. This compound appeared to be the "parent molecule" of the isolated constituents of this plant. Structural elucidation and characterization of isolated compounds were done by IR, 1H-NMR, MS, and GC-MS spectroscopy. The interrelationship of these compounds was also proven through chemical derivatization (methylation and acetylation. Preliminary testing of the smooth muscle relaxant activity of the oil showed that 5 x 10 -4(exponent) g/ml concentration of the oil completely inhibited a concentration of 1 x 10 -5(exponent) g/ml of ACh-induced contraction of the small intestines.